Icelandic doctors on a transnational labor market - Sveinsson, Kjartan Páll (School of Social Sciences, 2023)
Icelandic doctors responded to the financial crisis of 2008 by emigrating in great numbers. Between 2009 and 2014, 330 doctors emigrated from Iceland, while only 140 doctors returned. Consequently, Iceland witnessed the sharpest increase in inhabitants per doctor in its history, which resulted in a crisis within the healthcare sector. The article looks at how the structure of the labour market influences Icelandic doctors’ migratory decision-making. I argue that professional standards are equally important to wages as a factor influencing the doctors’ mobility and migratory trajectories, and that the main problem revolves around the work environment, particularly the structure of the healthcare system itself. The research is based on in-depth interviews with 20 doctors who have worked abroad but moved back to Iceland, 10 doctors who are working abroad with no plans to move back, and 15 policy makers within the healthcare sector. Læknar brugðust við áhrifum efnahagshrunsins 2008 með því að flytja af landi brott í miklum mæli. Á árunum 2009–2014 fluttu 330 læknar frá Íslandi á meðan einungis 140 læknar fluttu heim á sama tíma. Í kjölfarið fækkaði læknum meira en áður hefur sést hérlendis sé miðað við íbúa á hvern lækni. Þetta leiddi til erfiðleika innan heilbrigðiskerfisins. Í greininni eru áhrif vinnumarkaðarins á heimkomu íslenskra lækna erlendis frá skoðuð, sér í lagi hvernig þeir atvinnumöguleikar, sem í boði eru hvetja eða letja lækna til þess að flytja aftur heim. Þegar ástæður brottflutnings og heimkomu eru skoðaðar kemur í ljós að faglegur metnaður skiptir álíka miklu máli og laun til að útskýra hreyfanleika lækna. Meginvandamálið er fyrst og fremst tengt vinnuumhverfinu og þá sérstaklega sjálfu heilbrigðiskerfinu og uppbyggingu þess. Rannsóknin byggir á djúpviðtölum við 20 lækna sem hafa starfað erlendis en flutt aftur heim, 10 lækna sem starfa erlendis og sjá ekki fyrir sér að flytja heim og 15 aðila sem starfa í stjórnsýslu innan heilbrigðiskerfisins.